Risk factors of COVID-19 incidence in Bantul Regency, Indonesia - Wardani, Siska; Astuti, Fardhiasih Dwi (Intelektual Pustaka Media Utama, 2023)
Coronavirus disease 2019 (COVID-19) was a public health problem in Indonesia. The highest number of COVID-19 cases in Special Region of Yogyakarta in 2021 was in Bantul Regency. The epidemiological description based on the person, place, time, and risk factors for COVID-19 in Bantul Regency in 2021 has yet to be described. This study aimed to determine risk factors, person, place, and time characteristics associated with the incidence of COVID-19 in the Bantul Regency in 2021. This study employed a cross-sectional design with secondary data on COVID-19 cases in Bantul Regency in 2021. Furthermore, 80,322 samples were analyzed and confirmed COVID-19 was 53,506 cases (66.61%). The case fatality rate was 2.72%. The highest age positive for COVID-19 is <65 years (92.31%), 53.83% of cases were female, and the district of Banguntapan with the highest rate of COVID-19 (15.11%). The peak of cases occurred in July, 2021. There is a relationship between close contact, travel history, age, and gender with the incidence of COVID-19 (p<0.001). The most significant risk factors were close contact (OR=8.657), travel history (OR=3.034), gender (OR=1.147), and age (OR=0.889). Close contact has the most significant association with the incidence of COVID-19, followed by travel history and gender.